Analisis Strategi Marketing Public Relations di PT Lunar Chemplast - Hasna, Mintriati; Putriana, Muria; Kholik, Abdul (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
The productivity level of livestock in Indonesia is still very low. This is marked by a gap between the supply and demand for milk.. This is caused by the lack of business capital and the lack of knowledge or skills of farmers on how to raise livestock properly. Therefore, PT Lunar Chemplast is here to overcome this problem by providing livestock equipment and solutions. This research focuses on the Marketing Public Relations (MPR) strategy of PT Lunar Chemplast in increasing awareness among Indonesian farmers. This research uses a qualitative approach with descriptive analysis. Data was collected through interviews and observations of one key informant and two informants. Data analysis was carried out through the steps of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that PT Lunar Chemplast only uses 6 of the 7 Marketing PR tools: Publications, Events, Sponsorships, News, Public Service Activities, and Identity Media. Pull, push, and pass strategies are also applied to support Marketing PR activities. In addition, PT Lunar Chemplast employs effective communication methods to convey messages and information to farmers. The recommendations given in this study are that PT Lunar Chemplast needs to maximize Marketing PR activities by innovating and activating social media platforms as a means of publication.